Analisis Pengaruh Kepemimpinan dan Penilaian Kerja terhadap Kinerja Pegawai Pada Pemprov DKI Jakarta - Irma Asiho; Umar Usman; Slamet (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2024)
The purpose of this study is to determine how much influence the variables of leadership and job appraisal have on employee performance in the DKI Jakarta Provincial Government. How much influence does leadership have on employee performance. How much influence does work appraisal have on employee performance. The method used in this research is quantitative method, where data collection is used by distributing questionnaires and library data. The population of this study were all 45 employees. The sampling technique uses non probability sampling with saturated sampling type. The method used is multiple linear regression. The results of data processing using SPSS version 26 found that the results of multiple linear regressionY = 7.523 + 0.699 X¹ + 0.111 X². The results of data processing using SPSS version 26 found that R Square was 49.6%. This means that the contribution variables of leadership and work appraisal can explain the employee performance variable by 49.6%. influenced by other variables outside this regression equation or other causes. The results of this study concluded that partially seen from the results of the analysis on leadership (X¹), namely t count of 4.373 and t table of 1.682 with sig 0.000. Therefore, t count H0 is rejected and Ha is accepted, which means that leadership has a positive and significant effect on employee performance in the DKI Jakarta Provincial Government. Judging from the results of the analysis on job appraisal (X²), namely t count of 2.573 and t table of 1.682 with a sig of 0.000. Therefore, H0 is rejected and Ha is accepted, which means that work appraisal has a positive and significant effect on employee performance in the DKI Jakarta Provincial Government. Simultaneously, it can be proven by the test value of f count of 5.514 and f table of 3.21 with sig below 0.000. This means that leadership and work appraisal have a positive and significant effect on employee performance at the DKI Jakarta provincial government. Based on the conclusions above, leaders should include employees in the decision-making process and its implementation. Employees should also comply with the applicable regulations in pergub no.57 of 2020. Leaders should also provide the right direction and supervise the performance of each employee so that they are able to provide good quality work in carrying out their duties.